(3NeS YTQI LedI eNJUQI aj Yde GdcdGe hCUhd Ojf eMeO Ydjg GdSdGes - (3jMji Hf efUhQ Hf GdYaja Hf GdaVd Hf GdgGOj Hf jMji Hf GdMSfs ((3MSf Hf egOi Hf eMeO GdegdG s)
(3ChdgG (B:s
(3bGd jMji Hf efUhQ GdMeO ddg Pi GdQMeI hGdEfYGe hHYO aEf GdZQV HgPG GdeNJUQ GdcdGe ai eYQaI Led GdESdGe , hCUhd Ojf eMeO s
(3BNQgG (B:s
(3hdG bhd hdG Yed hdGfjI EdG HZUGHI GdSfI Zdi ZjQ Pdc ef cdGe Ydjg GdSdGe , aUM Gdbhd HhLhH GdYde HGdYGHOI GdSeYjI hGdYed HefbJVi GdTQjYI GdfHhjI Je s
(3HgG fXGe GdJYbjHIs
(3cJHJ ahGJMgG HGdSejcs
(3Ydi WQJgG Jedc HGSe eMeO Hf YHO Gddg Hf GdgGOi GdeMQGHis
(3hBNQ HGSe eMeO Hf eMeO Hf GdbGSe Hf Ydi Hf CejQ GdeDefjf hhdOg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3CUhd Gdabgs